Transisi Sistem Energi Global - Arfani, Riza Noer (UI Scholars Hub, 2006)
The article argues that global energy issue tends to be taken seriously and addressed only in the context of crises. The context should however be understood as a periodic transitional cycle of global energy system in which one energy source shifts to an alternative one in a cyclical and periodic energy system transition. Dynamic interaction among global energy actors will in turn affect and determine how the global energy system shifted and made its transitional mechanism. Their power relations are viewed here as reflecting their political economic relations in a global energy supply and demand interface. Four major factors affecting those dynamic interactions are recognized. First, the existence and role of any particular energy cartel such as OPEC (Organization of Petroleum Exporting Countries) in the case of petroleum-driven global energy system which is still continuing and nearly reaching its final phase. Second, the role of oil and the United States as dominant player in the existing global energy system. The two determine how the petroleum final phase as major energy source will be endured and eventually ended. Third, the roles of other key players in global energy with their diverse characters and growing numbers. Finally, the role and characteristics of global energy policies which cover issues such as technological, location and management dimensions. Careful observation on these four factors helps us describe how the new transitional period in global energy system will be initiated, developed and finally switched. This is a periodic cycle which in turn determines the existence and roles of global energy players. This is also a transitional cycle which affects how those players develop their interaction patterns. Finally, this is a cycle which determines the dynamics, orientation, characters, patterns and scenarios of future power struggle among nations and other key players in global energy issues.